Analisis Strategi Humas Polrestabes Surabaya Dalam Mempertahankan Citra Kepolisian - Bari sarifudin; Rudi Febrianto; Deni Firmansyah; Dyva Claretta (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
The image built by an institution needs to be maintained and developed, because the image certainly has an impact on public trust. The research entitled "Analysis of the Public Relations Strategy of the Surabaya Police in Maintaining the image of the Police" aims to determine the role and public relations strategy carried out by the public relations of the Surabaya police in maintaining the good image of the police. The method used by the researcher is descriptive qualitative. The results of this study show that the public relations of the Surabaya police use various public relations media to disseminate information and as an effort to develop a positive image of the police.